Reusing Newspaper Kiosks for Last-Mile Delivery in Urban Areas. - González-Varona, José Manuel; Villafáñez Cardeñoso, Félix Antonio; Acebes Senovilla, Fernando; Redondo, Alfonso; Poza García, David (MDPI, 2020)
The current increase in e-commerce is generating growing problems in urban areas in terms of both traffic flow (increasing traffic, no parking spaces) and environmental issues (noise, atmospheric pollution, etc.). In parallel, an iconic element of historic districts is disappearing: more and more newspaper kiosks are closing their business as their work dwindles. In this scenario, the objective of this paper is to propose a model for last-mile parcel delivery that exploits the current available newspaper kiosk network by using them as parcel lockers. To demonstrate the benefits of this proposal, we map the kiosk network of the city of Valladolid (Spain), and compare the environmental impact of a traditional (door-to-door) delivery and the proposed model which reuses old kiosks as parcel lockers. The necessary steps to carry out simulations are described in detail so that experiments can be replicated in other cities that face the same issues.
Keywords: Logística; Economía circular; E-commerce; Last-mile delivery; Urban logistics; Urban areas; Newspaper kiosk; Transformación digital